Liquid chromatography detectors - Scott, Raymond P. W. (Raymond Peter William), 1924-2011 (Journal of chromatography library ;, 1986)
The renaissance of liquid chromatography took place in the late 1960's and early 1970's. The first edition of this book published in 1977 described the detectors that were available at that time and which provided a performance matching that of the contemporary equipment with which they were associated. It is interesting to note that the most popular detectors then (the UV detector, the refractometer detector, the fluorescence detector and the electrical conductivity detector) are still the most commonly used detectors nearly a decade later. Detector design, however, has changed very significantly over the intervening years. Modern high efficiency columns provide very narrow peaks and very fast separations, and thus the physical design of the detectors had to change to meet these new challenges. In 1977, there was little real understanding of the important role played by the detector in the overall function of the chromatographic system and although some of the factors were pointed out in the first edition of this book, in retrospect they appeared to be little understood. This second edition gives an entirely new presentation of the subject of liquid chromatography detectors. It contains sections dealing with the fundamental aspects of the interaction between columns and detectors and the interaction between ancillary equipment and the detector. It brings the reader up-to-date with new designs and novel detecting systems that have been developed since 1977 and extends significantly the subject of the association of the liquid chromatography detector with spectroscopic techniques. In particular the book now explores the association of liquid chromatography with nuclear magnetic resonance, infrared and atomic absorption spectrometry. This book not only gives a comprehensive treatment of the subject of liquid chromatographic detectors and provides a rational procedure for defining their performance and so permit valid comparisons, but also discusses detector performance in relation to the whole of the chromatographic system.